2021
DOI: 10.1016/j.jebo.2020.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus infections and deaths by poverty status: The effects of social distancing

Abstract: We study the spread of COVID-19 infections and deaths by county poverty level in the US. In the beginning of the pandemic, counties with either very low poverty levels or very high poverty levels reported the highest numbers of cases. A U-shaped relationship prevails for counties with high population density while among counties with low population density, only poorer counties report high incidence rates of COVID-19. Second, we discuss the pattern of infections spreading from higher to lower income counties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 38 publications
2
35
0
3
Order By: Relevance
“…Research has found that high poverty communities have significantly higher rates of COVID‐19 cases and deaths than communities with lower poverty rates (Adhikari et al 2020; Jung et al 2020). For purposes of this study, it is also important to recognize that poverty rates are more extensive in rural compared with urban areas (Albrecht et al 2000; Lichter et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that high poverty communities have significantly higher rates of COVID‐19 cases and deaths than communities with lower poverty rates (Adhikari et al 2020; Jung et al 2020). For purposes of this study, it is also important to recognize that poverty rates are more extensive in rural compared with urban areas (Albrecht et al 2000; Lichter et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been several country-level and even regional level analyses of the outbreaks, the county-level analyses of COVID-19 in the U.S. have focused on the relationship between income and demographic variables and the case counts (see, e.g., [ 3 , 9 , 10 ]). Our results show that there are distinct patterns, and many counties exhibit a similar “signature” in the outbreak pattern.…”
Section: Discussionmentioning
confidence: 99%
“…This counter-intuitive relationship may be due, in part, to the complex interplay of the regional demographics that include the population density, the poverty level, and other variables. For example, Jung et al [ 10 ] showed that there was a U-shaped relationship between the poverty percentile in a U.S. county and the number of COVID-19 cases. Counties with both lower and higher poverty percentiles in the poverty distribution among counties experienced higher case counts early in the pandemic, while those near the median experienced lower case counts.…”
Section: Background and Significancementioning
confidence: 99%
“…Es en extremo difícil compararla con eventos similares de expresión aguda, en especial si ocurrieron en los albores del desarrollo científico del conocimiento médico y de la salud pública, donde el impacto global sólo puede equipararse con aquel causado por las grandes guerras o las depresiones económicas mundiales, o quizá con lo trémulo de los movimientos independentistas concretados durante los siglos XVIII y XIX, en virtud que el efecto colectivo y la consecuencia a largo plazo parece una condición inexorable. (Hozhabri et al, 2020;Jung et al, 2020) Tal atributo catastrófico de la COVID-19 al momento, son los más de 80 millones de enfermos contabilizados desde fines de diciembre de 2019 al cierre de 2020, con 1.8 millones de muertes atribuidas y un impacto negativo incalculable al orden mundial, pero más aún si consideramos que la oleada del proceso pandémico se mantiene activo (COVID-19 Corona Tracker, 2020); al tiempo en que no se había logrado concretar la evidencia científica de un tratamiento efectivo y las vacunas más prometedoras aún seguían en fase experimental, las menos en la antesala de su aplicación poblacional, y todo ello envuelto en una profunda incertidumbre atribuida más bien a un efecto infodémico y opacidad en los resultados experimentales para su concreción. (Crescioli et al, 2020;Ghazy et al, 2020;Hong y Kim, 2020;Mehrian-Shai, 2020;Parham et al, 2020;Won y Lee, 2020) La situación de México, vista en el contexto mundial, supuso en los albores de la pandemia una posición lejana, contrastado con algunos entornos devastados por la enfermedad, lo cual hoy está más lejos de ser cierto, en un sistema mundo interrelacionado, interconectado y en comunicación sincrónica instantánea.…”
Section: Introductionunclassified